Growth versus value investing: a case of Nigerian Stock Market - Mukail Aremu Akinde; Eriki Peter; Ochei Ailemen Ikpefan (Investment Management & Financial Innovations, 2019)
At a time, the Nigeria Stock Exchange (NSE) is generally undergoing bearish trends; the paper investigated the performance of eighty-eight (88) sampled stocks, which were screened with the modern Price Earnings Growth (PEG) ratio into the Growth and the Value Portfolios. This is to ascertain whether the Value Portfolio outperformed the Growth Portfolio in terms of returns. From the researches in the developed and emerging stock markets, the momentum supports that the Value Portfolio outscored the Growth Portfolio in terms of returns. The paper explored pooled data from the Factbooks of the Nigerian Stock Market and the Annual Reports across different industries from 1990 to 2016. Descriptive methods and Arellano and Generalized Methods of Moment (GMM) xtabond2 were adopted to address the outliers, reverse causality and other related consequences of panel data. Similar to the findings from the developed and emerging stock markets, the study recognized that the Value Portfolio over-performed the Growth Portfolio in terms of returns in the NSE. Therefore, it is recommended that rational investors should show more preferences to invest in low-priced Value Stocks to earn higher returns than the high-priced Growth Stocks, which generated lower returns in the NSE.